Attitudes towards Receiving Monkeypox Vaccination: A Systematic Review and Meta-Analysis - Mostafa Hossam-Eldin Moawad; Amira Mohamed Taha; Dang Nguyen; Mohammed Ali; Yasmine Adel Mohammed; Wesam Abd El-Tawab Moawad; Esraa Hamouda; D. Katterine Bonilla-Aldana; Alfonso J. Rodriguez-Morales (Vaccines, 2023)
Background: The public’s attitude towards Mpox vaccination is a critical factor in the success of immunisation programmes. Understanding the factors contributing to vaccine acceptance or hesitancy is critical for developing effective health communication strategies. This systematic review and meta-analysis aims to bring together evidence from observational studies on attitudes towards Mpox vaccination, including willingness and rejection. Methods: From this review’s inception until June 2023, a comprehensive search was conducted across four major electronic databases: PubMed, Web of Science, Scopus, and EBSCO. The inclusion criteria included studies investigating public attitudes towards Mpox vaccination, as defined by acceptance and willingness to be vaccinated versus rejection and unwillingness. Results: Thirty studies met the inclusion criteria among the screened literature. An analysis of 27 studies involving 81,792 participants revealed that 45,926 (56.14%) were willing to receive the Mpox vaccination. In contrast, ten studies involving 7448 participants revealed that 2156 people (28.94%) were unwilling to receive the Mpox vaccination. Females were less willing to receive the vaccine than males, with an odds ratio (OR) of 0.61 (95% CI, 0.43–0.86). Furthermore, homosexuals were found to be more willing than heterosexuals, with an OR of 1.44 (95% CI, 1.14–1.80). Conclusion: Vaccination is emerging as a critical strategy for preventing Mpox infection and fostering herd immunity against potential outbreaks. Improving public awareness and acceptance of vaccination is critical to avoiding a situation similar to the COVID-19 pandemic. Targeted educational and outreach programmes could explain the benefits of vaccination, bridging the information gap and encouraging a proactive public health approach to emerging infectious diseases.